Pressure Groups and the Democratic Process in Nigeria (1979-1993) (Nordic Journal of African Studies, 2002)
This paper examines the contributions made by pressure groups to the democratic process in Nigeria. The paper attempts a conceptualization of pressure groups and democracy. It also examines the relevance of pressure groups generally, as well as their attitude to and participation in the democratic process in particular. The specific contributions of these groups to the democratic process as well as obstacles to their effectiveness are discussed. The paper concludes by advocating the need for the groups to achieve a wider spread and to participate more actively in the democratic process as ways of becoming more relevant in the democratic process.